Improving Integral Concept Understanding Ability through ICT: Systematic Literature Review - Lina Nurhayati; Nurmala Setianing Putri; Bill Chairy Rizki Bustaren (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
Understanding the concept of integral is critical for engineering students, particularly civil engineering students. Many civil engineering students struggle to understand the concept of antiderivatives and the procedure for calculating integral. The objective of this study was to examine if technology, especially information and communication technology (ICT), can significantly improve civil engineering students' knowledge of the integral. The research sample comprises ten studies that employ diverse research approaches to investigate the impact of integrating ICT, including GeoGebra, Maple, MATLAB, and Other technologies, on enhancing knowledge of integral concepts. The method employed was a Systematic Literature Review (SLR) that followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. ERIC, SCOPUS, and Google Scholar-indexed journals published between 2012 and 2023 were sampled. The findings revealed that studying with Maple and Integrating technology has a significant impact on helping students comprehend integrals. It is demonstrated by the effect size values of 1,23 and 1,26, respectively.